Assessing the Options to Improve Regional Wheat Yield in Eastern Canada Using the CSM–CERES–Wheat Model. (1st March 2017) - Jing, Qi; Qian, Budong; Shang, Jiali; Huffman, Ted; Liu, Jiangui; Pattey, Elizabeth; Dong, Taifeng; Tremblay, Nicolas; Drury, Craig F.; Ma, Bao‐Luo; Jégo, Guillaume; Jiao, Xianfeng; et al.
Abstract : Core Ideas: Wheat yield at both field and regional scales was successfully simulated using CSM–CERES–Wheat. There is a considerable room to improve spring wheat yield in eastern Ontario. Average yield in eastern Ontario can reach 3600 kg ha −1 with fertilization at 100 kg N ha −1 . Crop models may need to include lodging—often related to high N rates in eastern Canada. Wheat ( Triticum aestivum L.) yield is relatively low in eastern Canada. This study aimed to assess fertilizer N management options to improve the regional yield of wheat using the CSM–CERES–Wheat model. The model was adapted to simulate winter wheat by replacing air temperatures with estimated temperatures under snow cover, and then the model was evaluated for simulating winter wheat using experimental data collected at two sites and spring wheat at three sites in eastern Canada. Across all the experimental years and sites, the normalized root mean squared error (nRMSE) between simulated and measured yields was 14%. Regional yield under rainfed conditions in the Eastern Ontario Region (a Census of Agriculture unit as a case study) was simulated with 0, 1, 1.5, and 2 times the recommended N rate (around 50 kg N ha −1 ) and unlimited N for the calibrated cultivars of spring wheat from 1981 to 1999. The simulated average regional yield (in dry matter) with the recommended N rate ranged from 2180 kg ha −1 for cultivar Hoffman to 2502 kg ha −1 for AC Brio. Both were close to the reported yield of 2440 kg ha −1, with nRMSE values ranging between 20.3 and 16.6%. The simulated regional yields with unlimited N were two times that with the recommended N rate, showing a considerable yield gap. Our simulations indicate that regional yield could increase to 3600 kg ha −1 in the Eastern Ontario Region if the N rate was increased to around 100 kg N ha −1, although a slight decrease in N use efficiency would occur. In addition, with such increases in the N fertilization rate, other abiotic factors such as lodging should be evaluated.